A Mixed Methods, Observational Investigation of Physical Activity, Exercise, and Diet Among Older Ugandans Living With and Without Chronic HIV Infection. (2nd November 2021) - Wright, Chelsea H.; Longenecker, Chris T.; Nazzindah, Rashidah; Kityo, Cissy; Najjuuko, Theresa; Taylor, Kirsten; Rentrope, Cynthia Robin; Webel, Allison
Abstract : Supplemental Digital Content is Available in the Text. Abstract: People living with HIV (PLWH) are at increased risk for cardiovascular disease. Physical activity, exercise, and controlled diet can mitigate this risk, yet these behaviors are understudied in sub-Saharan Africa. Our objective was to describe and compare the meaning, value, and patterns of physical activity, exercise, and diet among PLWH and older adults without HIV in Uganda. This mixed methods, observational study included 30 adult PLWH and 29 adults without HIV who (a) wore an accelerometer to measure physical activity; (b) had weight, height, and waist and hip circumference measured; (c) completed physical fitness measures; and (d) used digital cameras to record photographs and videos of their typical diet and physical activities. Participants were approximately 58 years old and 68% female. Approximately 20% of PLWH and 40% of adults without HIV met physical activity guidelines ( p > .05). Qualitative themes included engaging in a variety of exercise, structural barriers to exercising, and typical meals. Older adults in Uganda have low levels of physical activity and homogenous diets, increasing their risk for cardiovascular disease.